(untitled) (Research, Society and Development, 2021)
Abstract This paper aims to present a proposal for sustainable modernization of the productive model of babassu coconut bran, as a source of income expansion for the extractivist community of Ciriaco - MA. Observations of the work routine of the extractivist community of Ciriaco were used and an interview with the ATARECO coordinator to learn about the manufacturing process of products derived from babassu. The results showed that extractive workers have wasted the economic potential of the endocarp by discarding the process of extracting babassu almonds. The current production chain at the study site has no structure for large production demands because most of this process is carried out manually. The daily processing production at RESEX through the traditional is an average of 300 kg / day of babassu coconut, with the incorporation of machinery, the processing capacity becomes 20,000 kg of fresh coconut per day. Thus, there is a need to incorporate technologies in extractive activities in order to boost manufacturing and, consequently, the income of extractive families. Therefore, this work has relevance for raising indicators on the contribution of mechanized bran production derived from epicarp, mesocarp, and endocarp of babassu coconut, for the sustainable expansion of the income of communities that have babassu extractivism as a means of subsistence.